Treatment of industrial wastewater using constructed wetland : removal of orthophosphate and ammonia nitrogen - Anabil, Ubil (2008)
Industrial wastewater is one of the major concerns of the environment problems. As the wastewater is found to be highly contaminated, it could not be discharged directly into the environment. Therefore, wastewater treatment is essential to minimize the effect of the contaminants to nature. Based on previous studies, constructed wetland system (CWS) was proved to have high efficiency in treating industrial wastewater with low operating and maintenance cost. The industrial wastewater studied was Palm Oil Mill Effluent (POME) which was taken from Lepar Hilir Palm Oil Mill. In this research, lab scale of free water surface constructed wetlands was designed with the water lettuce (Pistia Stratiotes) as the wetland plant. The parameter studied including ammonia nitrogen (NH 3-N) and orthophosphate (Po 4 3- ). In order to investigate the effectiveness of the systems, three variables were studied which were the number of plant used (5, 10, 15), the wastewater concentration (87.5%, 75%, 62.5%) and the physical appearance of the plants during the treatment. The results showed that NH3-N was removed at high removal efficiency meanwhile Po 4 3- removal appeared at low removal efficiency. Both NH 3-N and Po